Programming microbes using pulse width modulation of optical signals. - Davidson, E; Basu, A; Bayer, T (2013)
Cells transmit and receive information via signalling pathways. A number of studies have revealed that information is encoded in the temporal dynamics of these pathways and has highlighted how pathway architecture can influence the propagation of signals in time and space. The functional properties of pathway architecture can also be exploited by synthetic biologists to enable precise control of cellular physiology. Here, we characterised the response of a bacterial light-responsive, two-component system to oscillating signals of varying frequencies. We found that the system acted as a low-pass filter, able to respond to low-frequency oscillations and unable to respond to high-frequency oscillations. We then demonstrate that the low-pass filtering behavior can be exploited to enable precise control of gene expression using a strategy termed pulse width modulation (PWM). PWM is a common strategy used in electronics for information encoding that converts a series of digital input signals to an analog response. We further show how the PWM strategy extends the utility of bacterial optogenetic control, allowing the fine-tuning of expression levels, programming of temporal dynamics, and control of microbial physiology via manipulation of a metabolic enzyme.